PALYNOLOGICAL, PALEOENVIRONMENTAL AND PALEOCLIMATE ANALYSES OF EMI-5-WELL, OFFSHORE NIGER DELTA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Palynological, Paleoenvironmental and Paleoclimatic investigations of Emi-5 well Offshore, Niger Delta, Nigeria was conducted to established palynozones, determine age, reconstruct paleoenvironmental conditions and paleoclimatic conditions to permit stratigraphic correlation, provide insights into the depositional settings and changes overtime within the basin. Fifty one (51) shaly ditch cutting samples were subjected to standard palynological method involving sample maceration with 10 % HCl and 40 % HF acids to remove carbonates and siliceous components, neutralization with distilled water and sieving through 5-micron sieve, followed by separation of palynomorphs from residue prior to mounting of the grains on glass slides for further analysis. The palynological composition is marked by dorminance of pollen and spores over dinoflagellate cysts. The intercalation of the sandy and shaly intervals across the section evidenced from lithologic, textural, and wire line log data suggested that the entire studied interval belong to the Agbada Formation. Three interval range zones were delineated using the international stratigraphic guide for the establishment of biozones, they are Stereisporites sp – Verrutricolporites rotundiporus; Verrutricolporites rotundiporus – Gemmemonoporites sp. and Retistephanocolpites gracilis – Pachydermites diederixi Zones and based on the aforementioned zones the interval is assigned middle Miocene to late Miocene. Coastal-deltaic environment of deposition is inferred for the studied interval on the basis of occurrence and dominance of diagnostic forms such as Zonocostites ramonae,Rhizophora, Psilatricoloporites crasssus and Acrostichum aureum while good representation of these forms and the identified palyno-ecological groups placed the interval on a wet climatic zone.
Keywords: Niger Delta; Emi-5-Well; Palynological zones; Paleoenvironment; Paleoclimate